The influence of information on the prevention of occupational risks and ergonomic requirements in the development of non-traumatic osteomuscular diseases of the shoulder – a pilot study - Rodríguez-Blanes, Gloria M.; Lobato-Cañón, José Rafael; Sánchez-Payá, José; Ausó-Pérez, José Ramón; Cardona-Llorens, Antonio Francisco J. (International journal of occupational medicine and environmental health, 2019)
Shoulder pain associated with upper limb musculoskeletal disorders is an important health problem in clinical practice due to its high prevalence, frequent consultations in primary healthcare and occupational health. Preventive strategies, including information disseminated among workers, can be useful. The aim of this study is to analyze the associations between non-traumatic osteomuscular diseases of the shoulder and the workers' knowledge of the risks at the workplace and preventive measures developed there, as well as the association with ergonomic requirements. An observational case-control study was carried out on an occupationally active population assisted during 1 year in 1 healthcare center, involving 690 participants. Data were collected through a questionnaire including sociodemographic variables, the workplace, the knowledge of prevention and ergonomic requirements. The independent effect of the variables associated with non-traumatic shoulder pathology was explored through logistic regression. In total, 66.7% of the participants stated that they had been informed of the occupational hazards related to their jobs. The following variables were associated with a lower probability of shoulder injuries: male gender, working hours > 9 h/day or > 40 h/week, as well as having information on the risks associated with the workplace, using personal protective equipment, the existence of an occupational risks prevention service and/or risk assessment, the knowledge of the prevention plan, periodic medical examinations, and using one arm or physical force at work. A multivariate analysis revealed that the risk increased with age and lower educational levels, forced postures, repeated gestures, monotony and temporary absences from work. Furthermore, being informed of workplace risks, and using a single arm as well as physical force were shown as independent protective factors. Information on both the ergonomic requirements and how to prevent occupational risks is a useful tool for the prevention of non-traumatic shoulder diseases. Preventive policies including health education interventions in the workplace could benefit other developed preventive activities. Int J Occup Med Environ Health. 2019;32(6):825-40.